Thinking Skills in Education: What Is the Alternative Approach to Educate Good Decision Makers? - Christina Andin, Nur Qistina Abdullah; Rohana, Hamzah; Mohd Shafiq, Abd Jabar; Mapjabil, Jabil; Muhamad Suhaimi, Taat (ijlrhss, 2021)
The development of thinking skills is recognized all over the world as one of the most important educational objective in the 21st century. In the Western world, the rationales that underlie in the need for developing students‟ thinking skills are always discuss from economic perspectives. However, concerns that are relating to the importance of thinking skill from those perspectives are limited to only the concept of solving problems related only to the worldly matter. Thus, this paper seeks to extend the discussion on the importance of thinking skills based on similar needs from Western and Islamic perspective which is to enhance thinking ability and also creates good judgement in decision making. Therefore, the focus is to analyse the gap exist in the current teaching of thinking skill approaches in the education field and invites us to reflect on the direction of our education for our current and next generation, especially within the context of choosing a suitable framework for cultivating students‟ thinking skills ability. Finally, this article proposes alternative approach in teaching thinking skill and how the approach will give impact in decision making with the value of justice.